Promosi Kesehatan Berbasis Sekolah pada Anak-Anak Sanggar Bimbingan Kuala Lumpur, Malaysia - Iskandar Iskandar; Yullyzar Yullyzar; Rahmad Rusyadi; Ubaidillah Ubaidillah (Universitas Pahlawan Tuanku Tambusai, 2026)
School-based health promotion is a strategic approach to improving children’s health, particularly among vulnerable groups such as migrant workers’ children. This community service program aimed to improve health knowledge and clean and healthy living behaviors among children at Community Learning Centre (Sanggar Bimbingan) in Kuala Lumpur. The program was implemented through basic health screening, health education sessions, demonstrations of clean and healthy living practices, and distribution of educational media to 25 participating children. Activities were conducted directly by a team of lecturers and students. The results showed that most children experienced minor health problems such as coughs, colds, and fever, had suboptimal vegetable consumption, and faced limited access to health services. After the intervention, the children demonstrated improved understanding of clean and healthy living behaviors, proper handwashing practices, and the importance of maintaining personal health. This program supports strengthening health promotion in non-formal learning communities.